ASSESSMENT OF LIFE QUALITY OF CERVICAL CANCER PATIENTS DELIVERED BLEOMYCIN ONCOVIN MITOCYN PLATINUM (BOMP) CHEMOTHERAPY REGIMENS IN SANGLAH DENPASAR - Noviyani, Rini; Budiana, I Nyoman Gede; Indrayathi, Putu Ayu (International Journal of Biosciences and Biotechnology; Vol 2 No 2 (2015))
Cervical cancer disease is one of cancers that attack many women in the world and ranks second afterbreast cancer. Symptoms of cervical cancer may cause degradation quality of patients life.Chemotherapy is one of treatments of cervical cancer patients. Chemotherapy provides therapeuticeffects, however, it can causes a decrease in life quality due to its side effects. BOMP is one ofregimens that can be used as one of the management of cervical cancer. Assessment of quality ofpatients life with cervical cancer are needed to see the changes in the quality of life in patients besidesknowing the functional status changes from time to time. Monitoring the effects of treatment, andcollecting the data on quality of life can be used as initial data for consideration in formulating theappropriate action for the patient, And also assist physicians in selecting an effective and welltolerated drug for patients.The study was conducted in February to June 2014 in Obstetrics Clinic andCempaka Timur Room General Hospital (RSUP) Sanglah in observational design with cross sectionalprospective. The sample selection is done by consecutive sampling. The methods used for datacollection using questionnaires EORTC QLQ with interview techniques before and afterchemotherapy in patients suffering cervical cancer of squamous cell stage IIB - IIIB who had BOMPchemotherapy regimens for 3 series in RSUP Sanglah. Research for quality of life is conducted ingeneral and the 15 domains that affect the quality of life of patients. In this study, 12 patients indicatedthe inclusion criteria. There were significant differences in the value of the quality of life of patientswith cervical cancer squamous cell stage IIB - IIIB before and after BOMP chemotherapy with 0.001p value. BOMP chemotherapy regimens can improved the quality of life of cervical cancer patientsincreasing from 44.833 ± 6.235 to 60.333 ± 9.168. In 15 ratings domain included decrease the qualityof life of pain domain, nausea domain, vomiting domain, decreased appetite domains, fatigue domain,physical function domain, functional role domain, social functioning domain, sleeplessness domain,constipation domain and domain of financial difficulties and on the other hand emotional domainincrease.
Keywords: Cervical cancer, quality of life, BOMP regimen, the domain of quality of life